Nontrivial Replication of Loci Detected by Multi-Trait Methods - Ning, Zheng; Tsepilov, Yakov A.; Sharapov, Sodbo Zh.; Wang, Zhipeng; Grishenko, Alexander K.; Feng, Xiao; Shirali, Masoud; Joshi, Peter K.; Wilson, James F.; Pawitan, Yudi; Haley, Chris S.; Aulchenko, Yurii S.; et al. (Frontiers in Genetics, 2021)
The ever-growing genome-wide association studies (GWAS) have revealed widespread pleiotropy. To exploit this, various methods that jointly consider associations of a genetic variant with multiple traits have been developed. Most efforts have been put on improving GWAS discovery power. However, how to replicate these discovered pleiotropic loci has yet to be discussed thoroughly. Unlike a single-trait scenario, multi-trait replication is not trivial considering the underlying genotype-multi-phenotype map of the associations. Here, we evaluate four methods for replicating multi-trait associations, corresponding to four levels of replication strength. Weak replication cannot justify pleiotropic genetic effects, whereas strong replication using our developed correlation methods can inform consistent pleiotropic genetic effects across the discovery and replication samples. We provide a protocol for replicating multi-trait genetic associations in practice. The described methods are implemented in the free and open-source R package MultiABEL.